HUBUNGAN PENGETAHUAN TENTANG TEKS DESKRIPSI DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 8 PADANG - Matisa, Anna Flora; Gani, Erizal; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This research is aimed to describe three things. First, to describe the knowledge of descriptive text of 7 grade student at SMP Negeri 8 Padang. Second, to describe the writing skill of descriptive text of 7 grade student at SMP Negeri 8 Padang. Third, to describe the relation between the knowledge of descriptive text and writing skill of descriptive text of 7 grade student at SMP Negeri 8 Padang. It was a descriptive research and using correlational analysis. The result revealed there is a correlation between the knowledge of descriptive text and the writing skill of descriptive text on 7 grade student at SMP Negeri 8 Padang. Thus, the knowledge of descriptive text is needed to write a descriptive text.Â Kata kunci: Hubungan, Pengetahuan, Keterampilan, Menulis, Teks Deskripsi